Structure, Properties, and Function of Glycosomes in Trypanosoma cruzi - Quiñones, Wilfredo; Acosta, Héctor; Gonçalves, Camila Silva; Motta, Maria Cristina M.; Gualdrón-López, Melisa; Michels, Paul A. M. (Frontiers in Cellular and Infection Microbiology, 2020)
Glycosomes are peroxisome-related organelles that have been identified in kinetoplastids and diplonemids. The hallmark of glycosomes is their harbouring of the majority of the glycolytic enzymes. Our biochemical studies and proteome analysis of Trypanosoma cruzi glycosomes have located, in addition to enzymes of the glycolytic pathway, enzymes of several other metabolic processes in the organelles. These analyses revealed many aspects in common with glycosomes from other trypanosomatids as well as features that seem specific for T. cruzi. Their enzyme content indicates that T. cruzi glycosomes are multifunctional organelles, involved in both several catabolic processes such as glycolysis and anabolic ones. Specifically discussed in this minireview are the cross-talk between glycosomal metabolism and metabolic processes occurring in other cell compartments, and the importance of metabolite translocation systems in the glycosomal membrane to enable the coordination between the spatially separated processes. Possible mechanisms for metabolite translocation across the membrane are suggested by proteins identified in the organelle’s membrane – homologs of the ABC and MCF transporter families – and the presence of channels as inferred previously from the detection of channel-forming proteins in glycosomal membrane preparations from the related parasite T. brucei. Together, these data provide insight in the way in which different parts of T. cruzi metabolism, although uniquely distributed over different compartments, are integrated and regulated. Moreover, this information reveals opportunities for the development of drugs against Chagas disease caused by these parasites and for which currently no adequate treatment is available.